2015
DOI: 10.1002/ccd.26139
|View full text |Cite
|
Sign up to set email alerts
|

Safety and feasibility of local myocardial hypothermia

Abstract: This study demonstrates the safety and feasibility of inducing intracoronary hypothermia by selective infusion of saline at room temperature in patients with SA and STEMI. Steady-state hypothermia could be achieved and maintained quickly, easily, and safely using common PCI techniques. Therefore, our findings warrant further studies to the use of intracoronary hypothermia to enhance myocardial salvage in acute myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
(64 reference statements)
2
11
0
Order By: Relevance
“…In this pilot study, selective coronary artery infusion of saline at 4°C by use of a modified aspiration catheter was rapid, effective, feasible, and safe in conscious STEMI patients, which was in agreement with the previous studies . Compared to the 2.8‐Fr infusion catheter with side‐holes and OTW‐Balloon described by Otterspoor et al , the modified aspiration catheter used in our study had some excellent properties, including rapid catheter exchange, blockage of blood flow, easy crossover of the lesion, tip injection of the cold saline and thrombus aspiration as required. The mean door‐to‐flow restoration times in our hypothermia group were prolonged with 13 min ( P = 0.07), which was consistent with previous studies .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this pilot study, selective coronary artery infusion of saline at 4°C by use of a modified aspiration catheter was rapid, effective, feasible, and safe in conscious STEMI patients, which was in agreement with the previous studies . Compared to the 2.8‐Fr infusion catheter with side‐holes and OTW‐Balloon described by Otterspoor et al , the modified aspiration catheter used in our study had some excellent properties, including rapid catheter exchange, blockage of blood flow, easy crossover of the lesion, tip injection of the cold saline and thrombus aspiration as required. The mean door‐to‐flow restoration times in our hypothermia group were prolonged with 13 min ( P = 0.07), which was consistent with previous studies .…”
Section: Discussionsupporting
confidence: 89%
“…Recently, this method has been tested in a human study. Otterspoor et al have confirmed the safety and feasibility of this local hypothermia by means of selective intracoronary infusion of saline at room temperature in the ischemia phase and at 4°C in the reperfusion phase at a rate of 10–30 mL/min in STEMI patients. It has been demonstrated that, using this cooling method in isolated beating pig heart model, the distal coronary temperature measured by temperature wire was approximately 2°C lower than the damaged myocardial temperature .…”
Section: Introductionmentioning
confidence: 93%
“…We report a prospective single center, single arm study of the safety and feasibility of transcatheter intracoronary hemodilution using unwarmed Hartmann's solution perfusate through the guiding catheter in patients undergoing PPCI for ST‐elevation myocardial infarction. Previous protocols have employed the use of a selective infusion catheter, placed at the location of the coronary stenosis to improve selective drug delivery. The use of a selective infusion catheter could result in increased time for equipment assembly and lead to delays to revascularization.…”
Section: Discussionmentioning
confidence: 99%
“…After successful PPCI of the culprit vessel, the guide wire was exchanged for one with distal pressure and temperature sensors (St Jude Medical, Minneapolis), whereafter distal coronary pressure, the index of microvascular resistance (IMR) and absolute flow were measured in the infarct-related artery as previously described in stable patients [9,10,12]. Maximal hyperemia, and thereby minimal microvascular resistance, was induced by using 140 μg/kg/min of intravenous adenosine via a central venous catheter.…”
Section: Invasive Hemodynamic Measurementsmentioning
confidence: 99%
“…This technique is based upon thermodilution using a continuous infusion of a low amount of saline through a microcatheter positioned selectively in a coronary artery. This technique is precise and not operator-dependent [9,10]. Measuring absolute blood flow and resistance has no meaning by itself as long as the distribution territory is unknown.…”
Section: Introductionmentioning
confidence: 99%